The smallest teeth in the world are caused by mutations in the PCNT gene - Kantaputra P. (2014)
We report a follow up study on two MOPD II Thai families with severe dental anomalies and hypoplastic alveolar bone. Striking dental anomalies comprise severe microdontia, opalescent and abnormally shaped teeth, and rootless molars. As a result of severe hypoplastic alveolar bone, most permanent teeth have been lost. Mutation analysis of PCNT revealed 2 novel mutations (p.Lys3154del and p.Glu1154X) and a recurrent mutation (p.Pro1923X). Teeth of the patient who carried a homozygous novel mutation of p.Glu1154X are probably the smallest ever reported. The sizes of the mandibular permanent incisors and all premolars were approximately 2-2.5mm, mesiodistally. All previously reported, PCNT mutations have been described to cause premature truncation of the pericentrin protein. p.Lys3154del mutation was unique as it was pathogenic as a result of missing only a single amino acid. In situ hybridization of Pcnt shows its expression in the epithelium and mesenchyme during early stages of rodent tooth development. It is evident that PCNT has crucial role in tooth development. The permanent dentition is more severely affected than the one. This implies that PCNT appears to have more role in the development of the permanent dentition. As pericentrin is a critical centrosomal protein, the dental phenotype found in MOPD II patients is postulated to be the consequence of loss of microtubule integrity which leads to defective centrosome function. © 2011 Wiley-Liss, Inc.